1986
DOI: 10.1073/pnas.83.10.3356
|View full text |Cite
|
Sign up to set email alerts
|

Efficient recovery and sequencing of mutant genes from mammalian chromosomal DNA.

Abstract: A retroviral shuttle vector was constructed by introducing the Escherichia coli xanthine (guanine) phosphoribosyltransferase gene (gpt) into the pZip-NeoSV(X)1 vector [Cepko, C. L., Roberts, B. E. & Mulligan, R. C. (1984) CeU 37, 1053-1062. This vector was packaged into infectious virus which then was used to infect a hypoxanthine (guanine) phosphoribosyltransferase-deficient mouse cell line. Cell lines that expressed the gpt gene were isolated, and it was found that these cells contained a single integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0
1

Year Published

1987
1987
1994
1994

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 34 publications
0
29
0
1
Order By: Relevance
“…lDneo. Infection of cells was carried out as previously described (1). Line HT1080neo is a population of cells derived from the human fibrosarcoma cell line HT1080 (32) by transfection with the plasmid pSV2Neo (42).…”
Section: Methodsmentioning
confidence: 99%
“…lDneo. Infection of cells was carried out as previously described (1). Line HT1080neo is a population of cells derived from the human fibrosarcoma cell line HT1080 (32) by transfection with the plasmid pSV2Neo (42).…”
Section: Methodsmentioning
confidence: 99%
“…The retroviral vector has long terminal repeats, which allow it to integrate into mammalian chromosomes; a simian virus 40 origin of replication, which enables it to be excised from the chromosome in the presence of simian virus 40 large T antigen (introduced through fusion with monkey COS cells, which constitutively produce the antigen) (4); a pBR origin of replication, which allows it to exist as an autonomously replicating plasmid in bacteria; and the bacterial neo gene, which can be used for selection of transformants in bacteria as well as in mammalian cells. In the initial studies on this system, one complicating factor observed was the relatively high rate of spontaneous mutants (around 10-5) (3). A high spontaneous mutation rate reduces the sensitivity of mutagen assays by limiting the lowest detectable frequency of induced mutation.…”
mentioning
confidence: 99%
“…The vector was used to transform bacteria, and the recovered gpt genes were sequenced. Experimental details of the various techniques have been published previously (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It allows selection of cell lines which have taken up DNA by transfection (8). It is also used in a variety of experiments which necessitate counterselection for loss of gpt activity either by inactivation of the gene (1,5,(11)(12)(13) or by deletion of the chromosome carrying the gene (2,10). In all instances, counterselection has been performed with the toxic purine analog 6-thioguanine.…”
mentioning
confidence: 99%